Analisa Kemampuan Mengajar Guru Matematika Dalam Beradaptasi dengan Kurikulum Baru Untuk Meningkatkan Performa Belajar Siswa - Cut Mega Hapsary; Fitriani; Nashiruddin; Novalia Zuhra (Yayasan Hurriah, Banda Aceh, 2020)
AbstractOne major concern in mathematics education in Indonesia is poor performance of student. This low achievement appears both in the National Assessment (UN) and international comparative study such as PISA and TIMSS. Many reasons have been advanced to explain these phenomena. Among the serious reasons are teacher instructions approach which much rely on traditional method, lack of mathematics activity doing by students in the classroom, lack of learning resources, and low motivation of teacher to face new change in 21th century education. Therefore, the aim of this study is to analyze teachers’ teaching practice in mathematics classroom to find the actual their problems so that the solution can be suggest. The study also discuss how rich mathematical tasks could be a potential solution for the problem. 10 mathematics teachers and 302 students from 6 junior high schools in Banda Aceh were involved in the survey. The study fond that the majority of teachers start using problem solving approach in teaching mathematics (74%), but the teaching process stil lacks to promote some subtansial aspects of peoblem based learning that such as mathematical connection, reasoning, and reflective thinking. The study also found that teachers mainly use text book provided by the ministry of education (87%) and their ability to desain students activities stil low. This indicates that the teacher face the real problem in conducting learning activities as mandated by new curriculum. The study suggests the rich tasks as a new approach to improve teachers’ teaching practice as well as to enhance students’ mathematics performance. AbstrackSalah satu desain task yang dapat dikembangkan guru adalah rich task. Beberapa penelitian menujukkan bahwa rich task mampu meningkatkan prestasi belajar siswa. Akan tetapi pendekatan ini jarang digunakan dalam pembelajaran matematika dengan berbagai alasan, sala satunya adalah kurangnya pemahaman guru mengenai pendekatan rich task. Oleh karena itu guru perlu dibekali dengan pendekatan ini agar prestasi belajar siswa dapat ditingkatkan. Penelitian ini untuk melakukan analisis awal mengenai berbagai kondisi objektif pembelajaran serta keadaan guru secara menyeluruh sehingga proses kolaborasi dalam mendesain kegiatan pembelajaran rich task selanjutnya akan dapat berjalan lancar. Hasil penelitian menunjukkan bahwa Guru matematika SMP di Kota Banda Aceh telah memiliki pengetahuan yang cukup untuk menjalankan profesinya sebagai pendidik matematika. Akan tetapi karena factor usia serta rendahnya tingkat kemanfaatan dari pelatihan yang dikuti dalam pembelajaran matematika sehari-hari menyebabkan proses pembelajaran matematika masih kurang melibatkan siswa untuk mengembangkan kemampuan berpikir tingkat tingginya. Aktivitas pembelajaran yang berorientasi pada kemampuan-kemampuan matematis seperti kemampuan koneksi dan berpikir reflektif jarang sekali dimunculkan.